2019
DOI: 10.1021/acs.cgd.8b01646
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Vapor Transport Crystal Growth of Hg3Se2I2 Hard Radiation Detector Using Organic Polymer

Abstract: The chalcohalide compound Hg3Se2I2 with a defect anti-perovskite structure has been demonstrated to be a promising semiconductor for room temperature X- and γ-ray detection. In this work, we use transport agents during the vapor growth of Hg3Se2I2 crystals under gradient temperature profiles to dramatically improve the size and yield of Hg3Se2I2 single crystals. Various growth conditions with combinations of organic polymer (polyethylene) with elemental Hg, Se, or I2 are compared. The largest single crystals (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…135 Furthermore, it is found that adding an organic polymer such as polyethylene (PE) can lead to significantly larger size and improved detector performance with the size up to 7 × 5 × 3.5 mm. 151 The Bridgman method, a melt-based technique, is also widely reported for the growth of inorganic perovskite SCs. 98 In this process, the sealed silica tube filled with the perovskite precursor is moved along the temperature gradient.…”
Section: Perovskite Single Crystalsmentioning
confidence: 99%
See 3 more Smart Citations
“…135 Furthermore, it is found that adding an organic polymer such as polyethylene (PE) can lead to significantly larger size and improved detector performance with the size up to 7 × 5 × 3.5 mm. 151 The Bridgman method, a melt-based technique, is also widely reported for the growth of inorganic perovskite SCs. 98 In this process, the sealed silica tube filled with the perovskite precursor is moved along the temperature gradient.…”
Section: Perovskite Single Crystalsmentioning
confidence: 99%
“…184 In addition, antiperovskite SCs such as TlSn 2 I 5 and Hg 3 Se 2 I 2 have also been made into vertical detectors, which display excellent performance for X-ray, γ-ray, and α-particle detection. 151,152 Studies to compare the performance of lateral and vertical photoconductors for X-ray detection were also conducted. 100 Recently, a very sensitive anisotropic X-ray detector made of 2D (NH 4 ) 3 Bi 2 I 9 SC has been reported.…”
Section: Direct Radiation Detectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 18–24 ] Benefiting from the advantages from the vapor‐phase growth method, the organic crystals made from the sublimated vapor can become the crucial parts in manufacturing high‐performance photonic and optoelectronic devices, such as organic solid‐state lasers (OSSLs), [ 25–27 ] organic optical waveguides, [ 28 ] organic field‐effect transistors (OFETs), [ 29,30 ] and organic photoelectric detectors. [ 31–33 ]…”
Section: Introductionmentioning
confidence: 99%